'Ardent sympathetic constellations' : Conceptualising Astropoetics and Cosmopoetics in the Twentieth-Century Novel - Klaeger, Florian (\CYRZ\CYRV\CYRE\CYRZ\CYRD\CYRE: \CYRK\cyrnje\cyri\cyrzh\cyre\cyrv\cyrn\cyra, \cyrje\cyre\cyrz\cyri\cyrch\cyrk\cyra, \cyru\cyrm\cyre\cyrt\cyrn\cyri\cyrch\cyrk\cyra \cyri \cyrk\cyru\cyrl\cyrt\cyru\cyrr\cyrn\cyra \cyra\cyrs\cyrt\cyrr\cyro\cyrp\cyro\cyre\cyrt\cyri\cyrk\cyra [STARS: Literary, linguistic, artistic and cultural astropoetics], 2024)
This essay introduces the concepts of astropoetics and cosmopoetics to describe literary manifestations of astroculture in the twentieth-century novel. It suggests that astropoetic texts are media of astroculture, bringing their formal conventions and traditions to bear on the particular questions raised by attempts to instil outer space with human meaning. For the student of literary history, astropoetics thus offers a specific window onto the history of poetics and criticism. Drawing on the history of metaphors and Hans Blumenberg’s metaphorology, the essay explores how these concepts illuminate the novel genre’s epistemology, ontology, and anthropology. By tracing the interplay between cosmic order and literary meaning, it argues that astropoetics and cosmopoetics offer a framework for understanding the novel’s potential for producing knowledge, its nature as ‘real’ or ‘imagined’, and its function as a medium of expression. The essay concludes by examining the ‘Ithaca’ chapter from James Joyce’s Ulysses as a key modernist text that exemplifies the self-reflexive potential of cosmopoetics in the novel.
Keywords: astropoetics; cosmopoetics; astroculture; poetics; twentieth-century novel; modernism; literary form; Hans Blumenberg; James Joyce; Ulysses